Modeling the Contribution of Traditional Sero Fisheries to Blue Economy Goals: Evidence from Rural Indonesia - Patangngari, Fijwal; Musbir, Musbir; Najamuddin (Faculty of Fisheries and Marine Universitas Airlangga, 2026)
Graphical Abstract Highlight Research 1. Artisanal sero fisheries in Bone Regency were assessed within the context of sustainable fisheries governance and the blue economy framework. 2. Six latent variables, economic characteristics, perceptions of fishing techniques, social factors, institutional dynamics, policy understanding, and regulatory compliance, were analysed using Structural Equation Modelling (SEM). 3. Socioeconomic status, institutional trust, and policy knowledge were found to be the strongest predictors of fishers’ compliance with fisheries regulations. 4. Strengthening fisher participation, promoting sustainable fishing education, and integrating sero fisheries into coastal zoning are key strategies to enhance compliance and support blue economy resilience. Abstract This study examines the integration of traditional sero (staked weir) fisheries in Bone Regency, Indonesia, into the sustainable governance and blue economy frameworks. Despite their socio-cultural importance, these small-scale fisheries remain undervalued in policy discourse and local management plans. This research utilizes Structural Equation Modelling (SEM) to assess fishers' perspectives and the factors driving regulatory compliance across six latent variables: economic characteristics, fishing techniques, social aspects, institutional dynamics, policy knowledge, and compliance behavior. The measurement model was empirically distinct, with all Heterotrait-Monotrait Ratio (HTMT) values below the 0.85 threshold. Key findings indicate that Policy Knowledge (C) has the most potent positive effect on compliance, with β = 0.902. Additionally, Livelihood Resilience (B) significantly affects compliance (β = 0.760), whereas Socioeconomic Characteristics (X) have a substantial adverse direct effect (β =- 1.003). Together, these variables explain a significant proportion of the variance in compliance behavior, with an R2 of 0.915. The results indicate that higher income, institutional trust, and strong community ties enhance compliance by enabling fishers to adopt sustainable practices. Conversely, economic instability hinders the application of policy knowledge. The study concludes that involving fishers in organizations and strengthening institutional support are vital for aligning artisanal practices with the blue economy. Implementing coastal spatial planning and adaptive interventions will help balance ecological preservation with the economic well-being of coastal communities.